Integrated mRNA and Small RNA Sequencing Reveals microRNAs Associated With Xylem Development in Dalbergia odorifera - Zhao, Wenxiu; Meng, Xiangxu; Xu, Jiahong; Liu, Zijia; Hu, Yangyang; Li, Bingyu; Chen, Jinhui; Cao, Bing (Frontiers in Genetics, 2022)
Dalbergia odorifera is a rare and precious rosewood specie, whose wood is a very high-quality material for valuable furniture and carving crafts. However, limited information is available about the process of wood formation in D. odorifera. To determine genes that might be closely associated with the xylem differentiation process, we analyzed the differentially expressed genes (DEGs) and microRNAs (miRNAs) from specific xylem tissues of D. odorifera by RNA sequencing (RNA-seq) and small RNA sequencing (small RNA-seq). In total, we obtained 134,221,955 clean reads from RNA-seq and 90,940,761 clean reads from small RNA-seq. By comparing the transition zone (Dotz) and sapwood (Dosw) samples, a total of 395 DEGs were identified. Further analysis revealed that DEGs encoded for WRKY transcription factors (eight genes), lignin synthesis (PER47, COMT, CCR2), cell wall composition (UXS2), gibberellin synthesis (KAO2, GA20OX1), jasmonic acid synthesis (OPR2, CYP74A), and synthesis of flavonoids (PAL2) and terpenoids (CYP71A1). Subsequently, a preliminary analysis by small RNA-seq showed that the expressions of 14 miRNAs (such as miR168a-5p, miR167f-5p, miR167h-5p, miR167e, miR390a, miR156g, novel_52, and novel_9) were significantly different between Dotz and Dosw. Further analysis revealed that the target genes of these differentially expressed miRNAs were enriched in the GO terms ‘amino acid binding’, ‘cellulase activity’, and ‘DNA beta-glucosyltransferase activity’. Further, KEGG pathway annotation showed significant enrichment in ‘fatty acid elongation’ and ‘biosynthesis of unsaturated fatty acids’. These processes might be participating in the xylem differentiation of D. odorifera. Next, expression correlation analysis showed that nine differentially expressed miRNAs were significantly negatively associated with 21 target genes, which encoded for proteins such as pyrH, SPL6, SPL12, GCS1, and ARF8. Overall, this is the first study on miRNAs and their potential functions in the xylem development of D. odorifera, which provides a stepping stone for a detailed functional investigation of D. odorifera miRNAs.